Sustainable Development of Renewable Energy Potential and Its Impact on Community Life in Indonesia: A Systematic Review - Dwijendra, Ngakan Ketut Acwin; Sanjaya, I Putu Ari; Armaeni, Ni Komang; Winastri K, Desak Ayu Krystina (ASTONJADRO, 2024)
Indonesia is very rich in new and renewable energy potential. Indonesia's population growth continues to increase and in line with technological advances that are developing very rapidly, causing the need for energy to increase. Problems related to resources and energy are still problems that have not found the right solution to overcome them. Society's dependence on fossil energy sources seems to make it difficult for new ideas and innovations for clean and affordable energy to enter people's lives. The purpose of this article is to find out the potential for new energy sources and renewable energy in accordance with the goals of the 2030 SDGs. The method used is a systematic literature review, by searching journal articles on renewable energy and successful case studies using Google search and Artificial Intelligence (AI) application review, while the data analysis technique is in the form of data reduction, data presentation to draw conclusions. The results of the study show that many cases show that if new renewable energy is well developed in Indonesia, this potential will become a very tangible benefit for people's lives. These potentials include the potential for solar power, biomass, and micro-hydro.